2013
DOI: 10.1016/j.wem.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Emergent Surgical Cricothyrotomy for use in Austere Environments

Abstract: Emergent cricothyrotomy is an infrequently performed procedure used in the direst of circumstances on the most severely injured patients. Austere environments present further unique challenges to effective emergency medical practice. Recently, military trauma registry data were searched for the frequency of cricothyrotomy use and success rates during a 22-month period. These data revealed that cricothyrotomy performed in the most rigorous austere environment (ie, battlefield) had many successes, but also a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 101 publications
2
51
0
Order By: Relevance
“…Discussion with multinational senior clinicians based at both the Role 3 and Role 1 echelons identified the perception of a lack of standardised approach and equipment as potential reasons for the complications associated with their findings 5. A review article in 2013 identified 12 distinct surgical cricothyroidotomy procedures and numerous variations of cricothyroidotomy equipment seemed to reinforce this concept 17. Common themes have appeared where training, simulation and practice are described as imperative for success 7 8 15 16 18.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion with multinational senior clinicians based at both the Role 3 and Role 1 echelons identified the perception of a lack of standardised approach and equipment as potential reasons for the complications associated with their findings 5. A review article in 2013 identified 12 distinct surgical cricothyroidotomy procedures and numerous variations of cricothyroidotomy equipment seemed to reinforce this concept 17. Common themes have appeared where training, simulation and practice are described as imperative for success 7 8 15 16 18.…”
Section: Discussionmentioning
confidence: 99%
“…At least 10 different surgical techniques have been described. 9 It is the opinion of the authors that the techniques described above offer several advantages: What equipment is required?…”
Section: Percutaneous Seldinger Kits Formentioning
confidence: 99%
“…9 It is the opinion of the authors that the techniques described above offer several advantages: What equipment is required? 9 It is the opinion of the authors that the techniques described above offer several advantages: What equipment is required?…”
mentioning
confidence: 99%
“…These advances are now crossing over to civilian EMS systems, tactical units, and wilderness medicine. [91][92][93][94][95][96][97][98] …”
Section: Military Medicinementioning
confidence: 99%